Non-invasive ventilation using RAM’S cannula in neonates-what difference does it make? - Anjuri Sharma; Monica Lazarus; Asha Tiwari; Lalit M Malviya; Vidya K Saurabh (Asian Journal of Medical Sciences, 2023)
Background: Neonates undergo transition at birth from breathing fluid to breathing air. If this change is not tolerated by neonate, need of assisted ventilation arises. Non-invasive ventilation (NIV) refers to any mode of respiratory support provided through nasal airway. Using RAM’S cannula as an interface, complications of invasive ventilation can be prevented, and therefore it can be impactful in improving respiratory care in neonates. Aims and Objectives: The aim of the study was to find the association of clinicoetiological factors and the outcome of NIV using RAMS’s cannula in neonates. Materials and Methods: This prospective observational study was done from March 1, 2021 to August 31, 2022 at Neonatal Intensive Care Unit of a Tertiary care center in Central India. Neonates given NIV through Ram’s cannula were enrolled. Primary diagnosis of subjects and clinical parameters - birth weight, gestational age, duration of NIV given, and severity of respiratory distress were recorded and analyzed to find an association with the outcomes. Informed consent was obtained from parents. Results: 100 neonates (62 male) were given NIV. 78 neonates were weaned off from NIV and 22 needed intubation. Duration of NIV, gestational age, severity of respiratory distress, and birth weight were found to be statistically significant. Weaning was more in gestation >34 weeks, weight >1 kg, duration of NIV given <3 days, and neonate having mild respiratory distress. Conclusion: NIV through RAM’s cannula is useful in both respiratory and non-respiratory illness. Higher rates of NIV failure were seen in the duration of NIV >7 days, weight <1 kg, and gestation <34 weeks.